The mental image of lightning in Lithuanian poetry - Kazlauskaitė, Rūta (Lietuvių kalba, 2018)
The aim of the present article is to compose and to evaluate the image of lightning that has been formed in Lithuanian poetry. The fragments of 148 poets’ 509 poems have been analysed. In the poetical worldview lightning is active. It is natural energy. It naturally manifests itself during the warm season and time of day (at evening, at night). Lightning usually acts as a living being (a human being, a reptile, less often as a bird or an ungulate), a plant or as a part of the body of a living being or a plant, an instrument of a living being. Less often lightning manifests itself as fire, water, earth. Lightning is compared and identified with the realities that are characterized by the following features: ‘glowing / bright / heated’, ‘sudden, short’, ‘formed in the heights, above’, ‘moving / moved’, ‘zigzag / twisting’, ‘increasing / branching out’, ‘powerful’, ‘piercing / sharp / hurting’.  The oppositional features ‘dull / extinguishing’, ‘slow, lingering’, ‘formed near the ground, below’, ‘calmed down / settled down’, ‘moving straight’, ‘vanishing, disintegrating’, ‘weak’, ‘streamlined’ show the approaching of lightning to a human being, its identification with a human being. Lightning in fact is defined by three features. The first one – the ability to strike: hit, cut, kick, scald, splash, etc. Lightning changes the current situation: injures or destroys, eliminates the object it points to (for example, cuts and cuts off, splits and splits up, stabs and pierces, burns and burns out). Thus the earth is cleaned up, renewed, refreshed. Lightings as instruments are ruled by the highest god of the Lithuanians, the ruler of nature Perkūnas, such mythical creatures as witch and devil, natural phenomena, the sky, the night, a human being (usually a young woman). The second feature – a specific manifestation or showing up of lightning. The electric current moving from above in zigzag or spiral (the metaphorical verbs bends, curls, twists, etc. are used) pulsates and increases (i.e. shines, flashes and grows, branches out, pours out). The third feature – the glowing and brightness of lightning. A special tone of light is shown by light, green, silver, fiery and similar epithets.  In the broad sense lightning is perceived as strength, life and illumination (the moment of change).
Keywords: lightning; poetry; mental image; attribute; meaning; metaphor